UNDERSTANDING THE CONCEPT OF RELIGIOUS HARMONY IN THE ANALYSING OF PHILOSOPHY OF RELIGION - Saumantri, Theguh (The Pontianak State Institute of Islamic Studies, 2025)
This research aims to enrich the understanding of the concept of religious harmony from the perspective of philosophy of religion, as well as to identify the contribution of philosophy of religion in enriching the understanding of religious harmony in the context of religious diversity in Indonesia. This research uses qualitative descriptive research methods with phenomenological approach. Based on the analysis conducted, it can be concluded that religious harmony is a fundamental concept in religious and societal life. This concept relates to values of tolerance, mutual respect, and understanding differences. Philosophy of religion can provide significant contributions in enriching the understanding of religious harmony by presenting basic concepts such as religious pluralism, tolerance and justic. Furthermore, philosophy of religion can also assist in identifying the root causes of challenges to religious harmony and provide strategies to overcome them. Thus, a deeper understanding of the concept of religious harmony from the perspective of philosophy of religion can help society in facing challenges to religious harmony and strengthening diversity in Indonesia